Analysis of the Impact of Pedestrian Revitalization in the City of Jombang Towards Pedestrian Convenience - Gredian Galu Sukma; Sri Wiwoho Mudjanarko (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Jalan Basuki Rahmad is one of the streets with a fairly active pedestrian routine because it is donated by a shopping area which is the center of the crowd and the lane near Jombang Station. However, the situation in the area is still lacking in good management, especially in the existing pedestrian facilities that look chaotic and unorganized. Rahmat Basuki Street is one of the streets in the center of the city so it needs to be arranged in order to create comfort for pedestrian users. One of the government's policies by rebuilding the pedestrian path is to revitalize. This research intends to discuss the effect of walkability and completeness of the road on pedestrian comfort on the pedestrian path on the Basuki Rahmad road in Jombang after being revitalized. The purpose of this study was to analyze the impact of revalitation in pedestrian structuring on the Basuki Rahmad Jombang road from the influence of walkability and completeness of the road to the pedestrian comfort on the Basuki Rahmad road in Jombang city. The method used is descriptive analysis and regression analysis. The results of the study showed that walkability and completeness of the road affected pedestrian comfort by 0.639 or 63.9% and 0.188 or by 18.8%.